Canine demodicosis: Associated factors, diagnostic approaches, and therapeutic evaluation - Supnesh Jain; Ranbir Singh Jatav; Rupesh Verma; Amita Tiwari; Rakesh Dangi; Aditya Pratap; Salil Kumar Pathak; Devendra Kumar Gupta (International Journal of Tropical Insect Science, 2026)

Galectin-3, transforming growth factor beta 1, and brain natriuretic peptide in cardiac remodeling under hyperlipidemic and hyperglycemic stress - Hina Patel; Angelie Pathak; Resmi Rajalekshmi; Brian David; Devendra K. Agrawal (Molecular and Cellular Biochemistry, 2026)
Hyperlipidemia (HYL) and hyperglycemia (HYG) directly drive pathological cardiac remodeling; however, the mechanisms by which these conditions differentially regulate profibrotic signaling and early stress‑response pathways in left ventricular (LV) myocardium remain poorly defined. This study investigated the expression and localization of galectin-3 (Gal-3), transforming growth factor-β1 (TGF-β1), and brain natriuretic peptide (BNP) in a Yucatan miniswine model of HYL and HYG. Female Yucatan miniswine were assigned to normal control, HYL (high-cholesterol diet), or HYG (high-fat/high-carbohydrate diet plus low dose streptozotocin) groups ( n = 6/group) for 8-weeks, and LV tissue was assessed by histology, qRT-PCR, Western blot, and immunohistochemistry. Both metabolic conditions induced cardiomyocyte hypertrophy and interstitial fibrosis, with more diffuse collagen deposition in HYG myocardium. qRT-PCR demonstrated upregulation of Gal-3, TGF-β1, and BNP relative to controls, with transcript levels positively correlating with circulating glucose concentration. Western blot analysis showed relatively greater active TGF-β1 signal in HYL myocardium and greater latent precursor accumulation in HYG myocardium, suggesting condition-associated differences in TGF-β1 regulation. Immunohistochemistry demonstrated perivascular Gal-3 localization, cytoplasmic and perinuclear TGF-β1 immunoreactivity in cardiomyocytes, and BNP immunoreactivity predominantly within subendocardial Purkinje fibers, with increased staining intensity in metabolically stressed groups compared with controls. Collectively, these findings suggest that HYL and HYG are associated with overlapping but distinct patterns of Gal-3, TGF-β1, and BNP expression during metabolic cardiac remodeling. The Gal-3/TGF-β1 axis may represent a shared profibrotic pathway, whereas BNP may reflect a compensatory stress response whose functional significance requires further mechanistic validation.

Colouration, growth performance and health status of ornamental koi carp (Cyprinus carpio var. koi) reared in variable stocking density under biofloc system - Amandeep Kaur; Amit Mandal; Sasmita Barik; Gurpreet Kaur; Devendra Pathak (Aquaculture, 2026)

Density-dependent growth, health, and bioeconomic performance of Asian stinging catfish (Heteropneustes fossilis) under biofloc culture - Lavanya; Amit Mandal; Chanchal Singh; Sasmita Barik; Devendra Pathak (Aquaculture International, 2026)

Endocrine architecture of caprine pancreas: a histomorphochemical and ultrastructural study - Kapil Dharmesh; Varinder Uppal; Anuradha Gupta; Devendra Pathak; Neelam Bansal (Journal of Molecular Histology, 2025)

Immunohistochemical and ultrastructural analysis of macrophages during cyclic corpus luteum formation and regression in Indian Buffalo - Kritima Kapoor; Opinder Singh; Devendra Pathak (Journal of Molecular Histology, 2025)

Seasonal modulation of progesterone receptor, PCNA, and enzyme activity in buffalo uterus: implications for endometrial growth during oestrous - Sagarika Dehury; Varinder Uppal; Devendra Pathak; Anuradha Gupta (Tropical Animal Health and Production, 2025)

Harnessing the Efficacy of a Rhizobium Strain in Individual and Consortium Mode to Promote Sustainable Lentil Production and Biofortification under Diverse Soil Conditions - Devashish Pathak; Devendra Singh; Manindra Nath Jha; Khushwant B. Choudhary (Journal of Soil Science and Plant Nutrition, 2024)

Recent advancement of nano-biochar for the remediation of heavy metals and emerging contaminants: Mechanism, adsorption kinetic model, plant growth and development - Himanshu K. Pathak; Chandra Shekhar Seth; Prabhat K. Chauhan; Gopal Dubey; Garima Singh; Devendra Jain; Sudhir K. Upadhyay; Padmanabh Dwivedi; Kuan Shiong Khoo (Environmental Research, 2024)

Genome-wide identification and annotation of SNPs and their mapping in candidate genes related to milk production and fertility traits in Badri cattle - Javid Ur Rahman; Devendra Kumar; Satya Pal Singh; Bijendra Narayan Shahi; Ashis Kumar Ghosh; Manish Kumar Verma; Abhishek Pathak; Aashaq Hussain Dar; Anil Kumar; Rabendra Kumar Sharma (Tropical Animal Health and Production, 2023)

Screening and Optimization of Zinc Removal Potential in Pseudomonas aeruginosa-HMR1 and its Plant Growth-Promoting Attributes - Ali Asger Bhojiya; Harshada Joshi; Sudhir K. Upadhyay; Abhishek K. Srivastava; Vinayak Vandan Pathak; Vimal Chandra Pandey; Devendra Jain (Bulletin of Environmental Contamination and Toxicology, 2022)

Climate risk insurance in Pacific Small Island Developing States: possibilities, challenges and vulnerabilities—a comprehensive review - Devendra Kumar Jain; Asif Chida; R. D. Pathak; Raghbendra Jha; Stephanie Russell (Mitigation and Adaptation Strategies for Global Change, 2022)

Prospecting catabolic diversity of microbial strains for developing microbial consortia and their synergistic effect on Lentil (Lens esculenta) growth, yield and iron biofortification - Abhinash Kumar; Manindra Nath Jha; Devendra Singh; Devashish Pathak; Mahendra Vikram Singh Rajawat (Archives of Microbiology, 2021)

Strategies for cryopreservation of testicular cells and tissues in cancer and genetic diseases - Tanushree Patra; Devendra Pathak; Mukesh Kumar Gupta (Cell and Tissue Research, 2021)

Ameliorative role of bosentan, an endothelin receptor antagonist, against sodium arsenite–induced renal dysfunction in rats - Ashwani Kumar Sharma; Japneet Kaur; Tajpreet Kaur; Balbir Singh; Harlokesh Narayan Yadav; Devendra Pathak; Amrit Pal Singh (Environmental Science and Pollution Research, 2021)

Immunohistochemical localization of estrogen receptor alpha (ERα) in the oviduct of Indian buffalo during follicular and luteal phases of estrous cycle - Devendra Pathak; Neelam Bansal; Opinder Singh; Kuldip Gupta; S. P. S. Ghuman (Tropical Animal Health and Production, 2019)

Estradiol attenuates ischemia reperfusion-induced acute kidney injury through PPAR-γ stimulated eNOS activation in rats - Amrit Pal Singh; Nirmal Singh; Devendra Pathak; Preet Mohinder Singh Bedi (Molecular and Cellular Biochemistry, 2019)

Deciphering the transcriptome of prepubertal buffalo mammary glands using RNA sequencing - Ratan K. Choudhary; Shanti Choudhary; C. S. Mukhopadhyay; Devendra Pathak; Ramneek Verma (Functional & Integrative Genomics, 2019)

Immunolocalization of Musashi1 and Fibronectin Type III Domain Containing 3B in Water Buffalo Mammary Glands - Harmanjot Kaur; Shanti Choudhary; Devendra Pathak; Opinder Singh; Ramneek Verma; Ratan K. Choudhary (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2018)

Camel Milk: An Important Natural Adjuvant - Raghvendar Singh; Gorakh Mal; Devendra Kumar; N. V. Patil; K. M. L. Pathak (Agricultural Research, 2017)

Dipyridamole attenuates ischemia reperfusion induced acute kidney injury through adenosinergic A1 and A2A receptor agonism in rats - Nikkita Puri; Vinita Mohey; Manjinder Singh; Tajpreet Kaur; Devendra Pathak; Harpal Singh Buttar; Amrit Pal Singh (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Laser-Induced Breakdown Spectroscopy and Phytolith Analysis: An Approach to Study the Deposition and Distribution Pattern of Silicon in Different Parts of Wheat (Triticum aestivum L.) Plant - Durgesh Kumar Tripathi; Rohit Kumar; Ashok Kumar Pathak; Devendra Kumar Chauhan; Awadhesh Kumar Rai (Agricultural Research, 2012)